Legal Annotation of Court Decision Number 75 / Pdt.Sus – Ipr / Merek / 2022 / Pn Niaga Jkt.Pst in Administrative Certainty for Famous Brands in Indonesia - Citraresmi Widoretno Putri; Suherman; Yuliana Yuli W; Beniharmoni Harefa; Satino (PT FORMOSA CENDEKIA GLOBAL, 2023)
Review of the trademark determination in court decision Number 75/Pdt.Sus-Hki/Merek/ 2022/Pn Niaga Jkt.Pst rejection of the application for the trademark GENHALILINTAR + Painting by Anofial Asmid because it was registered by PT SOKA CIPTA NIAGA on October 23 2017 with a Notification of Rejection Registration of the Mark